Introducing the New Testament : a historical, literary, and theological survey - Powell, Mark Allan, 1953- (Grand Rapids, MI : Baker Academic, 2009)
This up-to-date New Testament introduction has been carefully designed for the classroom. Mark Allan Powell presents disputed and controversial issues fairly, neither dictating conclusions nor privileging skepticism over faith-based perspectives. Chapters appear in the book in canonical order but are designed for assignment in any order. --from publisher description.
Preface -- The New Testament world -- The New Testament writings -- Jesus -- The Gospels -- Matthew -- Mark -- Luke -- John -- Acts -- New Testament Letters -- Paul -- Romans -- 1 Corinthians -- 2 Corinthians -- Galatians -- Ephesians -- Philippians -- Colossians -- 1 Thessalonians -- 2 Thessalonians -- The Pastoral Letters : 1 Timothy, 2 Timothy, Titus -- Philemon -- Hebrews -- James -- 1 Peter -- 2 Peter -- The Johannine Letters : 1 John, 2 John, 3 John -- Jude -- Revelation -- Glossary -- About the artwork -- List of maps -- Index.
Includes bibliographical references and index.
Keywords: Bible. -- Introductions